2013
DOI: 10.1007/s10549-013-2513-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-related longitudinal changes in depressive symptoms following breast cancer diagnosis and treatment

Abstract: Younger women being treated for breast cancer consistently show greater depression shortly after diagnosis than older women. In this longitudinal study, we examine whether these age differences persist over the first 26 months following diagnosis and identify factors related to change in depressive symptoms. A total of 653 women within 8 months of a first time breast cancer diagnosis completed questionnaires at baseline and three additional timepoints (6, 12, and 18 months after baseline) on contextual/patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(105 citation statements)
references
References 37 publications
4
98
3
Order By: Relevance
“…Because of diverse clinical manifestations and no standardized blood test to assess disease status, improvement of HRQoL is one of important treatment target in patients with SLE [11]. Depression has been consistently reported to have substantial impact on HRQoL of SLE patients in accordance with the current study [9][10][11]30,31]. It is noteworthy that depression was highly associated with extreme pain/discomfort in the present study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Because of diverse clinical manifestations and no standardized blood test to assess disease status, improvement of HRQoL is one of important treatment target in patients with SLE [11]. Depression has been consistently reported to have substantial impact on HRQoL of SLE patients in accordance with the current study [9][10][11]30,31]. It is noteworthy that depression was highly associated with extreme pain/discomfort in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…Considering that pain and depression share norepinephrine or serotonin neurotransmitter pathways, pain may result in depression and vice versa. Indeed, patients with cancer and depression experience more severe pain and have a worse prognosis than those without depression [31]. Considering fibromyalgia, characterized by generalized pain, was observed in 32% of patients with SLE in an earlier study [32], although we did not investigate fibromyalgia among the study patients, patients with extreme pain/discomfort might have fibromyalgia, which can influence mood and quality of life.…”
Section: Discussionmentioning
confidence: 89%
“…As indicated earlier, numerous studies report that younger women with breast cancer have an increased risk of depression, 18,27 and an increased risk of negative health consequences from breast cancer due to a reluctance to accept or comply with hormonal therapies that adversely affect marital intimacy. 29 We too found that younger age was associated with more depressive symptoms, especially in multivariate analyses that controlled for education.…”
mentioning
confidence: 89%
“…16 The highest rates of depression have been reported during the first year after diagnosis, 17 especially in women who are younger. 18 Women who receive adjuvant chemotherapy report more depressive symptoms, 19 which are thought to be due to the distressing side effects that chemotherapy can have (direct effects of chemotherapy on mood, energy level, cognitive functioning, and pain, which all interfere with activity). 20 Chemotherapeutic agents such as tamoxifen and aromatase inhibitors can induce sudden and intense menopausal symptoms in breast cancer patients, in whom estrogen replacement therapy is contraindicated.…”
Section: Introductionmentioning
confidence: 99%
“…The study was developed to evaluate age differences in adjustment to breast cancer. Study design has been previously described [27][28][29]. Briefly, eligibility criteria included first time breast cancer diagnosis, cancer stage I-III, completion of baseline survey within 8 months of diagnosis, at least 18 years of age (although no one in the study was younger than age 25), and ability to read and understand English.…”
Section: Setting and Populationmentioning
confidence: 99%